Mythological Xullyukuns in Beliefs of Yakuts (Sakha) (Expedition Materials) - Yu. A. Sleptsov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
Information about the mysterious supernatural water creature “xullyukun” is summarized in the article. It is emphasized that it takes its place in the pantheon of deities among the Yakuts (Sakha) — one of the indigenous peoples in the North-East of the Russian Federation. It is noted that Russian and foreign travelers, political exiles, and research scientists wrote about the traditions, life and religion of the Yakuts (Sakha) at different times. The descriptions of the beliefs of the Yakuts (Sakha) are given, in which there are references to the water creatures “xullyukuns”. The author has reviewed the literature where the “xullyukuns” are mentioned. The version proposed by scientists is analyzed, that “xullyukun” is a blending of the ancient spirit-master of water and an evil demon, which became possible due to the fact that this image correlated with the idea of the migration of aquatic animals from water to land and back. The author of the article is critical of such judgments. The data collected by the author of the article during numerous expeditions to the north-east of Yakutia, where the old image of the creature of the pre-Christian period has been preserved, is presented. On the basis of research, the author comes to the conclusion that the image of “xullyukun” is incomparable with the devil. It has been proved that “xullyukun”, according to ancient beliefs, is a creature — the arbiter of human destinies, and the new image is associated with Christmas divination, where the influence of Christianity is seen. The author of the article shares the original sources. Information collected in the field during conversations with informants is introduced into scientific circulation.